Requirements and design strategies for e-waste recycling management application - Mahmod, Musyrifah; Choy, Chee Wei (2019)
E-waste is one of the fastest growing waste streams in terms of its volume and impact on the environment globally. E-waste comprises of precious metals that can benefit the recycling industries but the hazardous chemicals needs to be properly disposed by the e-waste generators. This article reported on the process of developing e-waste recycling mobile application to be used by e-waste recycling players emphasizing on the requirement analysis and its system design. This application is developed to be used on mobile platforms guided by Rapid Application Development (RAD) methodology. A post study survey is conducted to get the user’s feedback on E-waste recycling mobile application.